Development of an android APP to calculate thermal comfort indexes on animals and people - Oliveira Junior, Arilson José (2018)
Nowadays, most of the analysis on thermal comfort in the agricultural environment, with particular reference to animal production environments, use indexes that allow the evaluation of the thermal stress level of a given location by means of climatological variables. For the resolution of these indexes there is currently no specific computational system that provides, in loco, the thermal condition of an environment. Thus, the present study aimed to develop a computational system capable of evaluating the thermal comfort of animal production facilities and human work environments. The system was based on the development of an application for smartphones and Android tablets, and the creation of a low cost portable device to measure climatological variables such as air temperature, black globe temperature and relative humidity. The portable device was developed based on the Arduino ATmega1280 microcontroller, along with temperature and relative humidity sensors. The android app was used together with the portable device in two environments, an office and a pig facility. The system showed to be functional in obtaining an in loco diagnosis of thermal comfort of the environments, in which measurements of air temperature, relative humidity and black globe temperature were collected and sent to the application that calculated THI and BGHI. The development of the Android application and portable device can be considered as a low-cost alternative solution for evaluations and monitoring of thermal comfort of animals and people.